2019
DOI: 10.30534/ijatcse/2019/6081.32019
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Software Product Quality using ISO 9126: A Systematic Review

Abstract: ISO 9126 software quality model of 2001 is the most comprehensive and widely accepted model. It is a generic quality model that is used in measuring quality of software across computing domains. This study seeks to access the level of application of ISO 9126 model in measuring software quality and its impact on different software domains. We employed a standard methodology for systematic literature review using automated search on four digital libraries for studies published between 2001 and 2016. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Risk document to become the basis of insurance price. Risk document must be aligned with ISO 9000 for quality assurance to develop application in order to following international standard models which are internal and external quality and quality in use or run the software application [16]. As can be seen above, five important points will be considered in the UBI device data, which will then be as a risk assessment tool for driving deaths.…”
Section: Results Of Discussionmentioning
confidence: 99%
“…Risk document to become the basis of insurance price. Risk document must be aligned with ISO 9000 for quality assurance to develop application in order to following international standard models which are internal and external quality and quality in use or run the software application [16]. As can be seen above, five important points will be considered in the UBI device data, which will then be as a risk assessment tool for driving deaths.…”
Section: Results Of Discussionmentioning
confidence: 99%
“…The research instrument used was based on the standard ISO 9126 for software development (Umar et al, 2019). Data gathering through a survey questionnaire was done first to know the current status of providing mock examination and the respondent's CPE results used to craft the system.…”
Section: Research Instrument / Data Collectionmentioning
confidence: 99%
“…The clients requirements and satisfaction is a popular saying and definition of the quality software [34]. According to a recent study [35], the author suggested that ISO 9126 software quality model of 2001 is broadly established and well-known model. The author further suggested regarding the significance of the model in assessing the quality of the software across diverse domains.…”
Section: Quality Management Success Factormentioning
confidence: 99%